Organizations and geographies of migration: The case of health professionals - Lang, Christine (ERDKUNDE, 2022)
Geographies of international migration are classically observed and described as spatial patterns of movements between nation states. This applies in particular ways to the migration of health professionals, whose spatial patterns are the object of much debate due to their consequences on healthcare provision and the reproduction of global inequalities. Often, the spatialities of this migration are explained by macro-level socioeconomic and institutional structures. This is paralleled by a widespread focus on the (inter)national scale. This paper aims to extend the perspective by exploring and conceptualizing the role of the meso-level of organizations in shaping geographies of migration. Based on the discussion of three crucial types of organizations involved in structuring and channelling mobility – state authorities, migration and labour-market intermediaries, and employers – the paper develops a framework for a systematic analysis of the organizational co-production of geographies of migration in the health sector and beyond. This draws attention to important mechanisms producing geographies of migration and allows a grasp of the role of various spaces other than nation states in the production of migration.